Pandemic culture: The impacts of COVID- 19 on the UK cultural sector and implications for the future - Abigail Gilmore; Dave O'Brien; Ben Walmsley (Manchester University Press, 2024)
This book reports on the findings of an eighteen-month UKRI funded mixed-methods research project that took place in England, Scotland, Northern Ireland and Wales between September 2020 and November 2021. It provides a comprehensive overview of the impacts of the Covid-19 pandemic on the UK's cultural sector, identifying implications for policy, practice and the sector's future direction. Over eleven chapters, the book summarises the local, regional and national policy responses to the crisis, and provides statistical analyses of the impacts on the UK's cultural workforce and audiences' responses to the pandemic. These insights are further illustrated via detailed case studies of cultural sub-sectors of theatre, museums and galleries, screen industries, libraries and festivals, interviews with cultural leaders and an ecosystem case study of the Greater Manchester city region. The book identifies recurrent themes emerging from the research, commenting on policy responses, audience confidence, shifts to digital engagement and civic responsibility, organisational practice and recovery. It offers a robust analysis of the short, medium and longer-term impacts of Covid-19 and highlights their implications for cultural practitioners, organisations, funders and policymakers. The unique contribution of the book lies in the presentation of findings which highlight the challenges faced by cultural practitioners, organisations and audiences from different backgrounds, regions and art forms. Using lenses which focus on both macro and micro levels, the book provides fresh insights into the implications for research on, with, and around the cultural sector, highlighting possible future directions for arts management, audience research and cultural policy studies.
Keywords: 300; Covid-19; cultural policy; creative and cultural occupations; arts management; mixed-methods research; audience research; inequalities; digital engagement; the civic role of the arts; cultural ecosystems